2017
DOI: 10.1093/infdis/jix076
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica–Encoded Homolog of Macrophage Migration Inhibitory Factor Contributes to Mucosal Inflammation during Amebic Colitis

Abstract: Understanding the mechanisms by which Entamoeba histolytica drives gut inflammation is critical for the development of improved preventive and therapeutic strategies. E. histolytica encodes a homolog of the human cytokine macrophage migration inhibitory factor (MIF). Here, we investigated the role of E. histolytica MIF (EhMIF) during infection. We found that the concentration of fecal EhMIF correlated with the level of intestinal inflammation in persons with intestinal amebiasis. Mice treated with antibodies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 49 publications
3
42
1
Order By: Relevance
“…Many parasitic pathogens, including E. histolytica , express a homolog of the pro-inflammatory cytokine macrophage migration inhibitory factor (MIF) [ 24 28 , 29 ••]. E. histolytica MIF ( Eh MIF) was recently shown to be a crucial parasite mediator of gut inflammation [ 29 ••]. A positive correlation was found between Eh MIF levels and intestinal inflammation in persons with amebic colitis.…”
Section: Inflammation and Macrophage Migration Inhibitory Factor Cytomentioning
confidence: 99%
See 3 more Smart Citations
“…Many parasitic pathogens, including E. histolytica , express a homolog of the pro-inflammatory cytokine macrophage migration inhibitory factor (MIF) [ 24 28 , 29 ••]. E. histolytica MIF ( Eh MIF) was recently shown to be a crucial parasite mediator of gut inflammation [ 29 ••]. A positive correlation was found between Eh MIF levels and intestinal inflammation in persons with amebic colitis.…”
Section: Inflammation and Macrophage Migration Inhibitory Factor Cytomentioning
confidence: 99%
“…A positive correlation was found between Eh MIF levels and intestinal inflammation in persons with amebic colitis. Eh MIF induced chemokine expression, neutrophil influx, and mucosal damage in cellular and mouse models of amebiasis [ 29 ••]. Also, Eh MIF enhanced TNF-α production by macrophages [ 25 ].…”
Section: Inflammation and Macrophage Migration Inhibitory Factor Cytomentioning
confidence: 99%
See 2 more Smart Citations
“…22 Notably, in in vivo experiments, it was shown that the anti-inflammatory cytokine IL-10 is protective in E. histolytica infection by counteracting an exaggerated proinflammatory immune response by inhibiting the production of proinflammatory mediators, such as TNF-α. 23 Interestingly, E. histolytica secretes cytokine-like proteins such as prostagrandin-E2 24,25 and mammalian inflammatory factor during tissue invasion, 26,27 which induces excessive proinflammatory responses by neutrophils at the infection site. Thus, neutrophils play a critical role both in the protection against tissue invasion by E. histolytica and in the promotion of tissue damage by E. histolytica.…”
Section: Roles Of Neutrophils In the Severity Of E Histolytica Infecmentioning
confidence: 99%